How to read Marx's Capital - Shapiro, Stephen, 1964- (How to read theory., 2008)
Capital Volume I is essential reading on many undergraduate courses, but the structure and style of the book can be confusing for students, leading them to abandon the text. This book is a clear guide to reading Marx's classic text, which explains the reasoning behind the book's structure and provides help with the more technical aspects that non-economists may find taxing. Students are urged to think for themselves and engage with Marx's powerful methods of argument and explanation. Shapiro shows that Capital is key to understanding critical theory and cultural production. This highly focused book will prove invaluable to students of politics, cultural studies and literary theory.